1995
DOI: 10.1002/pat.1995.220060514
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite materials from latex and cellulose whiskers

Abstract: Composite materials were processed by casting a mixture of aqueous suspensions of latex and microfibrils. These microfibrils, or whiskers, are extracted from a sea animal and are monocrystals of cellulose, with an aspect ratio around 100 and an average diameter of 20 nm. It has been found that the mechanical properties (shear modulus) are increased by more than two orders of magnitude in the rubbery state of the polymeric matrix, when the whisker content was 6% (w/w). This very large effect is discussed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
445
2
12

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 535 publications
(470 citation statements)
references
References 8 publications
11
445
2
12
Order By: Relevance
“…Similar trends are frequently reported for the dynamic mechanical analysis of cellulose nanocomposites. While a decrease in the peak height is generally observed with increasing filler content, a broadening and shift of Favier et al 1995).…”
Section: Mechanics Of Free-standing Coating Filmsmentioning
confidence: 93%
“…Similar trends are frequently reported for the dynamic mechanical analysis of cellulose nanocomposites. While a decrease in the peak height is generally observed with increasing filler content, a broadening and shift of Favier et al 1995).…”
Section: Mechanics Of Free-standing Coating Filmsmentioning
confidence: 93%
“…The materials prepared by solvent casting show optimized properties, since the long reaction time provides the particles enough time to interact and self-organize [70]. This self-organization generates a percolating network (a rigid 3D network), which will probably not form when using melt mixing process [71,72]. However, for economic and environmental reasons, the solvent casting method is a less efficient way to prepare composites when compared to other solvent-free processing techniques, such as hot processing.…”
Section: Pbat-based Compositesmentioning
confidence: 99%
“…Favier et al demonstrated that the addition of as little as 6% tunicate whiskers is sufficient to form a network that will strongly increase the storage modulus above the glass transition temperature. 4,5 Tunicate whiskers have high modulus and form strong interfibrillar bonds between ordered cellulose surfaces so that the network provides substantial stiffening to the rubbery matrix. Several reviews have been published on the subject of cellulose nanocomposites.…”
Section: Introductionmentioning
confidence: 99%